Biosynthesis of (R)‐(+)‐perillyl alcohol by Escherichia coli expressing neryl pyrophosphate synthase - Chao Sun; Rubing Zhang; Congxia Xie (Engineering in Life Sciences, 2022)
Abstract (R)‐(+)‐perillyl alcohol is widely used in agricultural and anticarcinogenic fields. Microbial production of (R)‐(+)‐perillyl alcohol was investigated in this study. We optimized biosynthesis of (R)‐(+)‐perillyl alcohol in Escherichia coli by using neryl pyrophosphate synthase and NADPH regeneration. Engineering neryl pyrophosphate (NPP)‐supplied pathway resulted in a 4‐fold improvement of (R)‐(+)‐perillyl alcohol titer. Subsequently, combined engineering of p‐cymene monooxygenase (CymA) expression and module for NADPH regeneration exhibited a 15.4‐fold increase of titer over the initial strain S02. Finally, 453 mg/L (R)‐(+)‐perillyl alcohol was achieved in fed‐batch fermentation, which is the highest (R)‐(+)‐perillyl alcohol titer in E. coli.